2019
DOI: 10.3390/w11020204
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Nitrogen Removal of Reject Water Generated from Anaerobic Digester Treating Sewage Sludge and Livestock Manure by Combining Anammox and Autotrophic Sulfur Denitrification Processes

Abstract: The reject water from anaerobic digestion with high (Total Nitrogen) TN concentration was treated by a demonstration plant combining the anammox process and SOD (SOD®; Sulfur Oxidation Denitrification) process. The anaerobic digestion was a co-digestion of livestock wastewater, food waste water, and sewage sludge so that the TN concentration and conductivity of the reject water were very high. This anammox plant was the first anammox demonstration plant in South Korea. The maximum TN removal efficiency of 80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…However, comparisons of this study with [20] are limited due to differences in the activity test methodology. When treating manure digestate dewatering liquors, Kwon (2019) [22] measured up to 90% of AMX retention in a system with an hydrocyclone, however there was also instability with periods of excessive AMX washout. The biomass washout for the different biomass types (e.g., AMX, AOB, and NOB) and Period 4 and Period 5 are presented in Figure 5.…”
Section: Biomass Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, comparisons of this study with [20] are limited due to differences in the activity test methodology. When treating manure digestate dewatering liquors, Kwon (2019) [22] measured up to 90% of AMX retention in a system with an hydrocyclone, however there was also instability with periods of excessive AMX washout. The biomass washout for the different biomass types (e.g., AMX, AOB, and NOB) and Period 4 and Period 5 are presented in Figure 5.…”
Section: Biomass Retentionmentioning
confidence: 99%
“…In a modelling study, Van Winckel (2019) [18] evaluated the impact of different SRTs on the biomass type (AOB, AMX, and NOB) and identified that greater AMX retention of 88-91% could lead to the enhanced nitrogen removal rate of 1.04-1.16 kg N m −3 d −1 . However, AMX washout from a hydrocyclone has also been observed [22]. Past studies that evaluated hydrocyclones are limited and relied on different ex-situ activity measurement methods with sample sizes of <5.…”
Section: Introductionmentioning
confidence: 99%
“…However, cyclones cannot retain all anammox bacteria, i.e. small anammox granules could be easily wasted out through overflows from the cyclones (Kwon et al, 2019), potentially leading to system failure. By contrast, anammox biocarriers could be easily retained in the system by screens (Han et al, 2016;Lemaire et al, 2014), indicating that the loss of anammox bacteria could be avoided.…”
Section: Anammox Biofilms Vs Granules In Mainstream Deammonificationmentioning
confidence: 99%
“…It has been suggested that the implementation of autotrophic denitrification or denitritation via sulphur for wastewater characterized by low COD/N ratio, could be very effective 14–16 . Wastewaters from a variety of industrial activities, such as mineral processes, sludge reject water, and landfill leachate, are effluent streams that due to their low C/N rate content will require the addition of an external carbon source during their treatment via heterotrophic denitritation/denitrification 3,17 .…”
Section: Introductionmentioning
confidence: 99%